Gagasan 1Malaysia melalui landasan seni & budaya - Lee, Lam Thye , 1946- (Jabatan Kebudayaan dan Keseniaan Negara, 2010)
Essays on Malaysian culture and art in supporting 1Malaysia concept, on-going political program and social policy designed by Najib Tun Razak